The volunteer's return: mutual benefit in community service and lived experience - Tilbury, Dane, author (Colorado State University. Libraries, 2026)
Most research on volunteering focuses on the people being helped—food banks track meals served, mentoring programs measure grades, animal shelters count adoptions. But what about the volunteers themselves? This thesis flips the question around to ask: What do volunteers gain from service, and how do those documented benefits hold up against real, lived experience? To answer this, I first conducted a literature review of nine academic studies spanning thirty years of research. The review looked at three main types of volunteer benefits: psychological and mental health improvements, social and cultural capital, and professional skills that transfer to the workplace. Then, I wrote a personal reflection chapter comparing the research to my own volunteer experience as president of a high school Unified Sports program, a youth little league coach, a two-year mentor for an at-risk youth through Partners, and a current veterinary assistant. The literature review found solid evidence that volunteering reduces depression, increases life satisfaction, builds social connections, and teaches valuable job skills. My own experience mostly lined up with those findings. But my reflection also uncovered things the research mostly misses: the emotional toll of caring for vulnerable people, the boring hours that still somehow matter, the messy way volunteer relationships often end without closure, and the fact that almost all the studies focus on older adults – not seventeen-year-olds like I was when I started. This thesis matters for public health, psychology, and service-learning programs because it backs up volunteering as a real way to improve mental health. But it also adds something the numbers alone cannot capture: the honest, complicated truth that volunteering does not always feel good. Sometimes it is frustrating or painful. But if you keep showing up, something changes anyway. Not a transaction. A transformation.
Keywords: volunteer